Genotype x environment interactions for yield components of broomcorn [Sorghum bicolor (L.) Moench] - Sikora Vladimir; Berenji Janoš (Selekcija i Semenarstvo, 2000)
The aim of this investigation was to study the ecological stability of yield components (weight of undressed and trashed panicle and seed weight per panicle) in fourteen varieties of broomcorn. Our current varieties was compared with our old, Hungarian and American varieties. Investigations were carried out under field conditions in a micro trial set up in a randomized block design providing five replications in seven ecologically different years. Stability parameters were computed using the model of Eberhart and Russell (1966). The results of this investigation showed that the genotypes differed in stability parameters for the characters studied. Variety Sava show good stability in all growing conditions. Variety Neoplanta plus was adapted to favorable and variety Reform to unfavorable conditions. Varieties with best performances in regard to yield components did not also show best stability. .